Electrical Properties of Fatty Acid in Salted Chitosan Membranes - M.Z.A. Yahya; R. Puteh; A.K. Arof (Institut Teknologi Bandung, 2004)
Films of chitosan polymer doped with lithium acetate (LiOAc) and placticized with oleic acid (OA) and palmitic acid (PA) were prepared by the solution cast technique. Impedance spectroscopy and XRD techniques have been used for the analysis. The film containing 40 wt.% LiOAc and 10.0 wt.% of OA exhibit a room temperature conductivity of 10-5 S cm-1 and the film containing 41.0 wt.% LiOAc and 7.7 wt.% of PA has conductivity 10-6 S cm-1. The plot of ln(σT) versus 103/T for the highest conducting samples obey an Arrhenian relationship in the temperature range between 300 and 363 K implying that the conductivity is thermally assisted. From conductivity-temperature studies the samples with high conductivity has low activation energies and vice-versa. The materials are ion conductors and the complex modulus formalism is further proof that the materials are ionic conductors.